2019
DOI: 10.1029/2019jd030832
|View full text |Cite
|
Sign up to set email alerts
|

Organic Aerosol Processing During Winter Severe Haze Episodes in Beijing

Abstract: Organic aerosol (OA) constituted a large fraction of aerosol particles during severe haze episodes in winter in northern China, yet our understanding of its physical and chemical processing was limited. Here we investigate the sources and processes of OA during four haze episodes in winter in 2016 using high-resolution aerosol mass spectrometer. The PM 2.5 reached 400 μg/m 3 during the severest episode (Ep1) when Beijing issued a red alert and implemented strict emission controls. Our results showed that secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
52
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 135 publications
25
52
3
Order By: Relevance
“…Such results are also supported by the large increase of non-volatile OA as elevated RH (Fig. S6), and the increases signal fraction of CHO + (m/z 29) in the mass spectra (7.2%-16.1%), a tracer ion related to aqueous processes (Zhao et al, 2019).…”
Section: Comparisons Between Volatile and Non-volatile Compoundssupporting
confidence: 57%
“…Such results are also supported by the large increase of non-volatile OA as elevated RH (Fig. S6), and the increases signal fraction of CHO + (m/z 29) in the mass spectra (7.2%-16.1%), a tracer ion related to aqueous processes (Zhao et al, 2019).…”
Section: Comparisons Between Volatile and Non-volatile Compoundssupporting
confidence: 57%
“…In particular, whether SOA materials condensed on BC particles have similar chemical characteristics to those externally mixed with BC particles 10 remains poorly understood. Previous observations in urban environments have reported that the mass spectral features of ambient OOA components identified by the PMF analysis were significantly different between the two co-located measurements even though their temporal variabilities strongly correlated to each other (Chen et al, 2018;Lee et al, 2017;Liu et al, 2019;Massoli et al, 2015;Wang et al, 2020;Xu et al, 2019;Zhao et al, 2019). Given our observations that vaporization scheme plays a critical role in the fragmentation process of oxygenated organic species,…”
Section: Insight Into Ambient Ooa Characteristicssupporting
confidence: 64%
“…Biomass burning, coal combustion, traffic, and dust are the key sources of PM (Sun et al, 2014a;Liu et al, 2018;Huang et al, 2014). Multiple studies have confirmed that biomass burning is an essential source of PM in urban Beijing (Gao et al, 2014;Sun et al, 2014a;Zheng et al, 2017). In this study, biomass burning and other solid fuel burning were identified as crucial sources of PM in not only urban but also rural areas of Beijing.…”
Section: Discussionmentioning
confidence: 66%